Preparation method and applications of 2-[2-chloro-N-(4-aminophenyl) acetamido]ethyl2-chloracetate - DAI CHUAN; ZHAO SHENGXUAN; CHEN YUYING (2015)
The invention relates to synthesis of a chemical preparation, and specifically relates to a preparation method and applications of 2-[2-chloro-N-(4-aminophenyl) acetamido]ethyl2-chloracetate. According to the preparation method, 2-(4-nitrophenyl)aminoethanol is taken as raw material, and is reacted with chloroacetyl chloride so as to obtain 2-[2-chloro-N-(4-nitrophenyl) acetamido]ethyl2-chloracetate (3); 2-[2-chloro-N-(4-aminophenyl) acetamido]ethyl2-chloracetate is prepared via reduction under Pd/C normal temperature hydrogenation catalysis; and NaOH is used for ring-closure reaction so as to obtain 4-(4-aminophenyl)morpholin-3-one. Nitro used for electron withdrawing is introduced firstly, so that bromine can be removed easily in subsequent nucleophilic substitution; and in addition, materials used in the preparation method are all solid, so that separation is more convenient; purification yield is high; the preparation method is suitable for enlarged preparation; and total yield is about 41.2%.